2005
DOI: 10.1021/jo050801q
|View full text |Cite
|
Sign up to set email alerts
|

Pd Nanoparticles as Efficient Catalysts for Suzuki and Stille Coupling Reactions of Aryl Halides in Ionic Liquids

Abstract: Pd-catalyzed Suzuki and Stille cross-couplings of aryl bromides and chlorides were carried out in quaternary ammonium salts as solvents under mild conditions and with the recycling of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(82 citation statements)
references
References 29 publications
1
81
0
Order By: Relevance
“…Additionally an ionic liquid phase containing the metal or metal oxide catalyst can be recycled several times without significant drop of yield. 23,[40][41][42] Nitrogen containing ionic liquids, such as imidazolium, pyridinium or pyrrolidinium ILs, with various counter anions are commonly used in nanocatalysis recycling experiments. 38,40,43 There are some reports about application of copper and copper oxide nanoparticles in ionic liquids, however most of them are related to electrochemistry and microelectronics and only very few report about application as catalysts in the wide field of organic synthesis.…”
mentioning
confidence: 99%
“…Additionally an ionic liquid phase containing the metal or metal oxide catalyst can be recycled several times without significant drop of yield. 23,[40][41][42] Nitrogen containing ionic liquids, such as imidazolium, pyridinium or pyrrolidinium ILs, with various counter anions are commonly used in nanocatalysis recycling experiments. 38,40,43 There are some reports about application of copper and copper oxide nanoparticles in ionic liquids, however most of them are related to electrochemistry and microelectronics and only very few report about application as catalysts in the wide field of organic synthesis.…”
mentioning
confidence: 99%
“…Based on their previous results 44,65,[68][69][70] that Pd colloids can promote the C-Cl activation, Nacci et al 71 reported the use of Pd nanoparticles obtained in ILs and water as catalysts in onepot sequential Heck-Mizoroki and Suzuki coupling reactions using bromo-chloroarenes or bromo-iodo-chloroarenes. The strategy allowed to prepare extended p-systems having a multisubstituted arene with different motifs as the basic skeleton.…”
Section: Heck-mizoroki Reaction In Ammonium Imidazolium Pyridinium mentioning
confidence: 99%
“…Palladium nano particles stabilized by tetraalkylammonium salts bearing long alkyl chains, have been proved to be an efficient catalytic system in C-C bond forming reactions such as the Suzuki and Stille cross-coupling reactions (Scheme 24). 122 Use of tetrabutylammonium hydroxide as a base in Suzuki coupling, enhanced the catalyst activity, and as a result the reactions proceeded smoothly under relatively mild conditions. In addition, the catalytic system can be recycled a number of times, and reused without loss of catalytic activity.…”
Section: Suzuki Couplingmentioning
confidence: 99%